Memaknai Teologi Penganiayaan dalam Teologi Paulus dari Perspektif Kebinekaan Indonesia - Halim Wona; Jefit Sumampow (Angelion, 2025)
This study focuses on interpreting the theology of persecution in Paul’s theology from the perspective of Indonesian pluralism, aiming to explore the relevance of suffering within the faith context of Christian minorities in a diverse society. Paul perceives suffering not merely as a tragic reality but as participation in Christ’s redemptive work and an expression of faithfulness to the Gospel. This research employs a qualitative-descriptive approach with theological and contextual analysis of Paul’s texts (particularly 2 Timothy 2:1–10, Romans 8, and Philippians 3), supported by empirical data from national and international journals concerning the experiences of minority churches in Indonesia. The findings indicate that the theology of suffering can serve as a source of spiritual resilience, communal solidarity, and an ethical foundation for peace and social justice. However, this theology must be understood critically so as not to justify injustice passively, but rather to encourage active engagement toward reconciliation and social transformation. Penelitian ini berfokus pada pemaknaan teologi penganiayaan dalam teologi Paulus dari perspektif kebinekaan Indonesia, dengan tujuan menggali relevansi penderitaan dalam konteks iman Kristen minoritas di tengah masyarakat plural. Paulus memandang penderitaan bukan sekadar realitas tragis, tetapi sebagai partisipasi dalam karya penebusan Kristus dan sarana kesetiaan terhadap Injil. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan analisis teologis dan kontekstual terhadap teks-teks Paulus (khususnya 2 Timotius 2:1-10, Roma 8, dan Filipi 3), serta data empiris dari jurnal nasional dan internasional terkait pengalaman gereja minoritas di Indonesia. Hasil penelitian menunjukkan bahwa teologi penderitaan dapat menjadi sumber ketahanan spiritual, solidaritas komunal, dan dasar etis untuk perdamaian dan keadilan sosial. Namun, teologi ini harus dipahami secara kritis agar tidak menjadi pembenaran pasif atas ketidakadilan, melainkan dorongan aktif menuju rekonsiliasi dan transformasi sosial.